Analysis of the attitude of scholars of the late Qing dynasty towards Christianity through the "Essay on Christianity" by Fang Junshi - Xiaojuan, Wang (Sinología hispánica. China Studies Review, 2021)
Fang Junshi was born to the Fang family clan in Dingyuan, Anhui Province, in the late Qing period. He enjoyed a certain prestige within the political world and literary circles of that time. His work Essay on Christianity continues with the thought of "Western knowledge of Chinese origin" from Wei Yuan's work, Illustrated Treatise on the Maritime Kingdoms, and analyzes and distinguishes the origin of Christianity, considering that it comes from Buddhism and Taoism. In An Illustrated Treatise on the Maritime Kingdoms, Fang Junshi supplemented information on relevant documents of Catholicism that had not yet been included and made a more in-depth analysis of the different data with his own explanations. In this way, Fang demonstrated the common attitude among late Qing scholars about Christianity, loosely upholding the Sinocentric attitude of Chinese civilization. The emergence of this phenomenon possibly derives from the following reasons: the prohibition of Christianity for more than a century since the middle of the Qing period, the actions perpetrated by missionaries after their entry into China and the evolution of the other relevant religions of that period.